Strategi Pengembangan Pariwisata Berkelanjutan di Desa Cihideung Udik Berbasis Lingkungan Pada Fasilitas Penunjang Pariwisata - Sofiani Sofiani; Tatiana Putri Yulia (HOSPITALITI DAN PARIWISATA, 2023)
The tourism industry should be developed in a sustainable manner based on taking into account environmental sustainability. Cihideung Udik Village is one of the villages located in Bogor Regency which is in the Ciampea sub-district. Cihideung Udik Village has a lot of tourism potential. Starting from the good cultural values ​​of the people, this village also has very beautiful landscapes such as waterfalls, agricultural land and a very beautiful environment and the air is cool. Then the most important thing is that this village is blessed with very abundant water sources. So it's no wonder that in the village of Cihideung Udik there is a water dam which the local people often call the Ciproy Dam, which stands for "Cihideung Project". The problem that arises is that there are still many inappropriate tourism supporting facilities. The research design used in this study is a qualitative descriptive study using the SWOT method. And the results of the research are that Cihideung Udik Village has internal and external potential for sustainable tourism which can be developed even further. Analysis of potential based on aspects or criteria as the concept of a tourist village shows that of the seven aspects, only aspects of the readiness of community human resources and aspects of tourism support facilities that still need to be improved, while the other five aspects namely; tourist attraction, community motivation, facilities and infrastructure, institutions and availability of land in general are sufficient to become a tourist village. The development of sustainable tourism in the village of Cihideung Udik is quite good, it's just that it needs improvement so that in the future Samangki village can become one of the pilot tourism villages in Indonesia. Keywords: Development Strategy, Tourism Village, Sustainable Tourism.